Revue Des Doses d’Exposition Et Des Methode d’Optimisation En Tomodensitometrie (TDM) De l’Enfant Au Togo - Tchaou, M.; Gnakadja, G.N.; N’timon, B.; Sonhaye, L.; Amadou, A.; Agoda-Koussema, L.K.; Adjenou, K.; N’dakena, K. (European Scientific Journal, ESJ, 2016)
Objectives: To assess the justification of indications of CT scans and the exposure doses of children during CT scans. Methods: Prospective study of 104 CT-sans of children collected over a period of 6 months. Results: Female children were predominant with a sex ratio female / male of 1.2. The predominant age group was the 10 to 15 years (41%). The CT-Scan of the head was the most practiced exam, with 64.42% (67/104). When analyzing information according to the recommendations of the Guide of well practices of French Society of Radiology (SFR) and the French Society of Biophysics and Nuclear Medicine (SFBMN), only 77% of CT-Scans were justified. Almost half (49.04%) of CT-Scans had a CT-Dose Index (CTDI) and Dose Length Product (DLP) greater than the French reference norms defined for each group of age. The average values of CTDI and DLP are above the norms for all CT-scans of the skull, facial bones and sinuses. Conclusion: The doses administered to children by CT-Scans are above accepted norms. Improved practices continue medical training of radiology manipulators and the creation of a regulatory or an agency of radioprotection is necessary.